Total Cot of Ownership of Electric Car and Internal Combustion Engine Car With Performance Normalization - Santoso, Adhe Budi; Priyono, Bambang (International Journal of Environmental, Sustainability, and Social Science, 2026)
In the transportation sector, motorized vehicles are currently a contributor to pollution in Indonesia, producing CO2 emissions. In an effort to achieve environmentally friendly and low-carbon motorized vehicles, promoting electric cars to the public is an important strategy that is being pursued by countries throughout the world. The large target of converting ICE cars to electric cars requires a series of analyzes to accelerate efforts to convert the use of electric cars from various angles which will ultimately be successful as a promotional medium for potential electric car users. To carry out this analysis, there is one calculation method, namely calculating the total cost of ownership (TCO) of an electric car. This method has been studied in countries that are concerned with promoting the use of electric cars. In this research, we will present a calculation model for the TCO of electric cars and the TCO of conventional internal combustion engine (ICE) cars as a comparison. The cars analyzed in this research consist of several electric cars and ICE cars according to their respective performance levels, where for each electric car an analysis of several battery ownership schemes is also attempted, namely those owned by the car owner, rental batteries and those owned by the car owner. However, some components can be repaired. The calculation model will consist of capital and operational costs, namely the purchase price, resale value, government subsidies, retailer discounts, battery replacement costs, maintenance, insurance, vehicle tax and energy consumption costs.